2017
DOI: 10.1002/poi3.154
|View full text |Cite
|
Sign up to set email alerts
|

Design Matters! An Empirical Analysis of Online Deliberation on Different News Platforms

Abstract: Ever since the Internet has provided easy access to online discussion, advocates of deliberative democracy have hoped for an improved public sphere. This article investigates which particular platform features promote deliberative debate online. We assume that moderation, asynchronous discussion, a well‐defined topic, and the availability of information enhance the level of deliberative quality of user comments. A comparison between different types of news platforms that differ in terms of design (a news forum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 60 publications
7
69
2
28
Order By: Relevance
“…Not all opportunities for deliberation produce constructive public engagement and may potentially empower ‘mischief and abuse’ (Lackaff , p. 142; see also Aragón et al ). Platforms that encourage discourse moderation, provide information, and clearly define topics (Esau et al ) and that recruit reasonably diverse and open‐minded participants will improve deliberation (Garard et al ).…”
Section: Challenges and Opportunities For Harnessing The Power Of Plamentioning
confidence: 99%
“…Not all opportunities for deliberation produce constructive public engagement and may potentially empower ‘mischief and abuse’ (Lackaff , p. 142; see also Aragón et al ). Platforms that encourage discourse moderation, provide information, and clearly define topics (Esau et al ) and that recruit reasonably diverse and open‐minded participants will improve deliberation (Garard et al ).…”
Section: Challenges and Opportunities For Harnessing The Power Of Plamentioning
confidence: 99%
“…More recently, Esau et al () observed forums on news websites and Facebook, and examined how different designs can influence the debate. Based on Friess and Eilders (), their study also concludes that platform architecture—which they term “institutional input”—“enables and fosters deliberation” (Esau et al, , p. 4).…”
Section: Participation and Architectures Of E‐parliaments: The Use Ofmentioning
confidence: 99%
“…The literature suggests that design is one of the most important features for shaping the characteristics of online deliberation and debate, and most researchers working on this subject have focused their analyses on comparing different structures (Esau, Friess, & Eilders, ; Jensen, ; Papacharissi, ; Sousa, ; Zittel, ). These works analyzed the effects of aspects such as moderation, availability of information, identification, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Isso agrega ao modelo a característica da replicabilidade para outras pesquisas, mesmo que haja limitações, as quais serão reconhecidas e apresentadas mais adiante. Além disso, comparações entre diferentes mecanismos (website e rede social, por exemplo) não seriam novidade no campo, uma vez que outros estudos, especialmente aqueles de deliberação online REZENDE, 2016;ESAU et al, 2016), já realizaram esse tipo de investigação, ao estudar comentários postados em páginas no Facebook, no Youtube e em blogs de política. Tais estudos, todavia, não se preocupam com uma análise unificada do desenho de diferentes mecanismos participativos, de que o modelo aqui apresentado pretende dar conta, por isso, optou-se pela diversidade de ferramentas para o estudo.…”
Section: Questão De Pesquisa Objetivos Corpus Empírico E Técnicas Dunclassified